New Gold-Catalyzed Reactions and Applications for the Synthesis of Alkaloids - Escribano Cuesta, Ana.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Ana Escribano Cuesta's thesis presents a detailed study of the inter- and intramolecular reactions of carbonyl compounds with 1,6-enynes using gold (I) complexes. An important part of the work involved streamlining the variables that allow the selective synthesis of different products such as tricyclic compounds, dihydropyrans, 1,3-dienes or cyclobutenes. The second chapter highlights the importance and difficulties in synthesising a cyclobutene subunit and the author includes a detailed description of how the products were prepared. The final chapter outlines the synthesis of lundurines using methodology developed by the author's research group for intramolecular gold-catalyzed cyclization of indoles with alkynes. The lundurine products developed in this work show significant in vitro cytoxicity toward B16 melanoma cells. The work in this thesis has led to a number of publications in high-profile chemistry journals.
Introduction -- General Objectives -- Gold(I)-Catalyzed Reactions of 1,6-Enynes with Aldehydes: Cycloaddition versus Metathesis-Type Reactions -- Formation of Cyclobutene Compounds via Gold(I)-Catalyzed Cycloisomerization of 1,n-Enynes -- Approach Toward the Total Synthesis of Lundurines.
Keywords: Chemistry; Chemistry, Organic; Catalysis; Chemistry; Organometallic Chemistry; Catalysis; Organic Chemistry